Shape Memory Hydrogels for Biomedical Applications - Aleeza Farrukh; Sana Nayab (Gels, 2024)
The ability of shape memory polymers to change shape upon external stimulation makes them exceedingly useful in various areas, from biomedical engineering to soft robotics. Especially, shape memory hydrogels (SMHs) are well-suited for biomedical applications due to their inherent biocompatibility, excellent shape morphing performance, tunable physiochemical properties, and responsiveness to a wide range of stimuli (e.g., thermal, chemical, electrical, light). This review provides an overview of the unique features of smart SMHs from their fundamental working mechanisms to types of SMHs classified on the basis of applied stimuli and highlights notable clinical applications. Moreover, the potential of SMHs for surgical, biomedical, and tissue engineering applications is discussed. Finally, this review summarizes the current challenges in synthesizing and fabricating reconfigurable hydrogel-based interfaces and outlines future directions for their potential in personalized medicine and clinical applications.